PROFIL PROTEIN ULAT SAGU (Rhynchophorus ferrugenesis) YANG DIGORENG DAN DIPANGGANG MENGGUNAKAN METODE SDS-PAGE - Noverson Lidaya; Stalis Norma Ethica; Ana Hidayati Mukaromah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Sago larvae is one of typical foods in papua, which rich of proteins containing various  types  of  essential  amino  acids  and  having  economic  value.  Papuan people use sago larvae as a source of income and for consumption. The heat processing on the worm could lead to protein denaturation. The objective of this research was to investigate the characteristic change of protein band pattern on sago larvae sample by SDS-PAGE method. Results of the study showed that the process of frying with time variations of 2, 4 and 6 minutes was proved to cause denaturation of sago larvae protein indicated by the missing of protein bands observation on electrophoregram. The highest level of sago larvae protein denaturation occured on sample fried for 6 min. There were only 4 minor protein bands with molecular weight of 60 kDa, 42 kDa, 40 kDa, and 31 kDa. Observed on the roasting process, there was no significant change in protein profile of the sample roasted for 2 to 6 min, but sample roasted for 4-min appeared to begin losing protein band on gel. As conclusion based on the experiment performed, the best time for frying and roasting of sago larvae is 2 min. Keywords: Sago larvae, Frying, Roasting, Protein profile, SDS-PAGE.